MiR-145 encapsulated small extracellular vesicles inhibit colorectal cancer progression by downregulating fascin actin-bundling protein 1 expression - Yanxia Chen; Meijuan He; Lei Cui; Jianguo Zhang; Hanpeng Huang; Zhimin Tao (Stem Cell Research & Therapy)
Abstract Background Drug degradation poses a significant challenge in the pursuit of effective gene therapies for cancers. Methods Here we have developed a bioactive nanosized composite that utilizes human umbilical cord mesenchymal stem cells (hucMSCs) derived small extracellular vesicles (sEVs), to carry tumor suppressor miR-145 alongside erbium-doped rare earth nanoparticles (ErNPs). This approach not only enhances in vivo delivery but also facilitates real-time fluorescence tracking of nucleic acid drugs in the near infrared (NIR) II window. With this technique, we are able to realize and visualize the effective inhibition of colorectal cancer (CRC) progression in a xenografted murine model. Results Our results revealed that the efficient loading of miR-145 into sEVs could be achieved through a dynamic combination of sonication and electroporation. The resulting miR-145-encapsulated sEVs (i.e., miRNA@sEVs) exhibited a profound ability to hinder tumor growth by effectively downregulating the expression of fascin actin-bundling protein 1 (FSCN1), both in vitro and in vivo. Additionally, the circulation half-time of miRNA@sEVs was measured to be ~ 4 h and the fluorescence at the tumor sites reached a peak intensity at ~ 8 h after intravenous injection of sEVs particles. Finally, the fluorescent signals of miRNA@sEVs were predominantly localized in the mouse liver and spleen, with substantial accumulation in tumors. Conclusions Our results illuminated the excellent biosafety of miRNA@sEVs and their high accumulation in tumors, leading to efficient suppression of tumor progression. This research heralds a promising advancement in gene therapy, paving the way for more effective and safer treatment options. Clinical trial number Not applicable.